Resilience of Historical Heritage The Existence of Wiwitan Tradition within the Dynamics of Farmer Groups in the Modern Era - Hana Khaeru Nisa; Sujono Sujono; Budi Wijayanto (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Agriculture is an inseparable part of agrarian culture; however, current agricultural modernization risks eroding local traditional practices due to its focus on efficiency, productivity, and economic gain. This study aims to analyze the relationship between farmer group dynamics and the existence of the Wiwitan tradition in Sindumartani Village, Ngemplak District, Sleman, Yogyakarta. Using a quantitative approach, research was conducted on 35 respondents from two farmer groups with distinct characteristics: the Tani Rukun group, which still preserves the tradition, and the Ngudi Mulyo 1 group, which no longer practices it. Data were collected using likert scale questionnaires and analyzed through correlation tests. The results indicate that the group development and maintenance variables have a very strong positive correlation (r = 0,722; Sig = 0,000) with the existence of the tradition. Furthermore, group goals and group cohesiveness variables show a significant positive correlation at a moderate level (r = 0,448 and 0,450, respectively). Conversely, group structure, task functions, and group effectiveness do not show statistically significant relationships. This study concludes that farmer group dynamics, particularly in the aspects of development and cohesiveness, play a crucial role in maintaining the continuity of the wiwitan tradition amidst the currents of modernization.